2021
DOI: 10.1158/0008-5472.can-20-2931
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial and Functional Interaction of a Heterotetramer Survivin–DNA-PKcs Complex in DNA Damage Response

Abstract: Substantial evidence has shown that overexpression of the inhibitor of apoptosis protein (IAP) survivin in human tumors correlates significantly with treatment resistance and poor patient prognosis. Survivin serves as a radiation resistance factor that impacts the DNA damage response by interacting with DNA-dependent protein kinase (DNA-PKcs). However, the complexity, molecular determinants, and functional consequences of this interrelationship remain largely unknown. By applying coimmunoprecipitation and flow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It was recently reported that upon ionizing radiation Survivin interacts with DNA-PKcs supporting NHEJ [23]. To analyze whether Survivin interacts with components of HR, we co-immunoprecipitated Survivin in the nuclear fraction of LN229 cells exposed to 50 µM TMZ for 48 h and conducted mass spectrometry-based proteome analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that upon ionizing radiation Survivin interacts with DNA-PKcs supporting NHEJ [23]. To analyze whether Survivin interacts with components of HR, we co-immunoprecipitated Survivin in the nuclear fraction of LN229 cells exposed to 50 µM TMZ for 48 h and conducted mass spectrometry-based proteome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As TMZ causes cell cycle arrest in the G2-phase, the main repair pathway of TMZ-induced DSBs is HR. A supporting function of Survivin in the repair of ionizing radiationinduced DSBs by NHEJ in glioma cells has been suggested [22] and the physical and spatial interaction of Survivin with DNA-PKcs in irradiated cells recently verified [23]. To elucidate the impact of Surv-GFP and SurvNESmut-GFP on induction and repair of DSBs after TMZ treatment, γH2AX foci formation was analyzed as surrogate marker for DSBs.…”
Section: Tmz Induces More Dsbs In Survnesmut Clones and Upon Survivin Knockdown In Parental Cellsmentioning
confidence: 99%
“…CO‐IP assay was performed as reported in detail previously 34 . Briefly, HEK293T cells were co‐transfected with CCDC124‐HA and CCDC124‐flag plasmids using Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…By this, Survivin accumulates in the nucleus and interacts with a prime non-homologous end joining repair factor DNA-dependent protein kinase (DNA-PKcs) [67,68]. Survivin forms a heterotetramer complex with DNA-PKcs that results in a conformational change on the DNA-PKcs phosphoinositide 3-kinase domain with enhanced enzymatic activity and detection of differentially abundant phosphopeptides and proteins implicated in the DNA damage response [69].…”
Section: Survivinmentioning
confidence: 99%